Overview of the Physical Condition of Pencak Silat Athletes - Fitri, Febrisa; Irawan, Roma; Suwirman, Suwirman; Haryanto, Jeki (Universitas Negeri Padang, 2021)
This research was conducted against the background of the low performance of the pencak silat athlete at Camar Putih Padang which is thought to be influenced by the physical condition of the athlete himself. This study aims to determine the level of physical condition of pencak silat athletes at the Camar Putih Padang College. This type of research is quantitative research using descriptive research methods. The population is 40 people and the sample is 22 people. Data collection was carried out by testing leg muscle explosive power, arm muscle explosive power test, agility test and aerobic endurance test. The analysis technique uses descriptive analysis techniques. Analysis of research data using the calculation of the percentage of P = F/N x 100%. With the results of the study 1) the explosive power of the male and female athletes' limb muscles was categorized as very good 2) the arm muscle explosive power test of male athletes was categorized as moderate while female athletes were categorized as very good 3) the agility test of male and female athletes was categorized as very poor 4) endurance test Aerobics was categorized as moderate while female athletes were categorized as good. It can be concluded that the level of physical condition of the pencak silat athletes from Camar Putih Padang is in the medium category.